2016
DOI: 10.1007/jhep01(2016)174
|View full text |Cite
|
Sign up to set email alerts
|

The a-function in six dimensions

Abstract: Abstract:The a-function is a proposed quantity defined in even dimensions which has a monotonic behaviour along RG flows, related to the β-functions via a gradient flow equation. We study the a-function for a general scalar theory in six dimensions, using the β-functions up to three-loop order for both the MS and MOM schemes (the latter presented here for the first time at three loops).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…As we have observed already in four dimensions [10,32] and six dimensions [33], and indeed at lower orders in three dimensions [21,22], the a-function coefficients are determined completely (within a given renormalisation scheme) up to the arbitrariness parametrised by the coefficientã.…”
Section: Consistency Conditions For Four-loop Anomalous Dimensionsupporting
confidence: 65%
“…As we have observed already in four dimensions [10,32] and six dimensions [33], and indeed at lower orders in three dimensions [21,22], the a-function coefficients are determined completely (within a given renormalisation scheme) up to the arbitrariness parametrised by the coefficientã.…”
Section: Consistency Conditions For Four-loop Anomalous Dimensionsupporting
confidence: 65%
“…If the kinetic terms of the theory possess a global symmetry, then β I in (1.1) is replaced by a generalized function B I , which begins to differ at three loops [5], and is related to the possible existence of theories with limit cycles [20]. While the effects of this shift have been included for the simple case of six-dimensional φ 3 theory [21] and the more complicated four-dimensional scalar-fermion theory [5], equivalent analyses for general gauge theories have not yet reached the point where considering this shift is necessary [6]. All quantities in Osborn's equation are given as functions of the couplings and group structures of the theory.…”
Section: The Long Versionmentioning
confidence: 99%
“…This is perhaps not surprising, as it has already been shown that the first off-diagonal contributions to T IJ in a general theory occur at three loops [6]. When deriving constraints on the β(B)-functions, imposing symmetry on T IJ would correspond to identifying the coefficients of each pair of tensors related by the interchange of open indices I and J, and setting them equal-in six-dimensional φ 3 theory at sufficiently high loop order, it has been shown that this does indeed force an additional CC, which (rather amazingly) turn out to be satisfied by the MS coefficients, and renormalizationscheme independent [21]. Effectively, we conjecture that it is always possible to choose local counter terms such that T IJ is symmetric, and that an analogous construction can be made in the extension to all even dimensions.…”
Section: Imposing Symmetry On T Ijmentioning
confidence: 99%
“…The beta-functions and anomalous dimensions for such a general sextic coupling were calculated in [37,38]; see also [39,40] for earlier results on the O(n) invariant sextic theory. The diagram topology contributing to the leading two-loop beta function is shown in figure 12.…”
Section: Renormalized Perturbation Theorymentioning
confidence: 99%